Cost-effectiveness of maintenance niraparib with an individualized starting dosage in patients with platinum-sensitive recurrent ovarian cancer in China - Shi, Yin; Xiao, Di; Li, Shuishi; Liu, Shao; Zhang, Yu (Frontiers in Pharmacology, 2023)
Objective: Niraparib improved survival in platinum-sensitive recurrent ovarian cancer (PSROC) patients versus routine surveillance, accompanied by increased costs. Based on the NORA trial, we evaluated for the first time the cost-effectiveness of maintenance niraparib with individualized starting dosage (ISD) in China. Methods: A Markov model was developed to simulate the costs and health outcomes of each strategy. The total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs) were measured. One-way and probabilistic sensitivity analysis were performed to estimate model robustness. Scenario analyses were also conducted. Results: Compared to routine surveillance, niraparib additionally increased QALYs by 0.59 and 0.30 in populations with and without germline BRCA (gBRCA) mutations, with incremental costs of 10,860.79 and 12,098.54, respectively. The ICERs of niraparib over routine surveillance were 18,653.67/QALY and 39,212.99/QALY. At a willingness-to-pay (WTP) threshold of 37,488/QALY, the ISD enhanced the likelihood of cost-effectiveness from 9.35% to 30.73% in the gBRCA-mutated group and from 0.77% to 11.74% in the non-gBRCA mutated population. The probability of niraparib being cost-effective in the region with the highest per capita Gross Domestic Product (GDP) in China was 74.23% and 76.10% in the gBRCA-mutated and non-gBRCA mutated population, respectively. Niraparib was 100% cost-effective for National Basic Medical Insurance beneficiaries under the above WTP thresholds. Conclusions: Compared to routine surveillance, the ISD of niraparib for maintenance treatment of PSROC is cost-effective in the gBRCA-mutated population and more effective but costly in the non-gBRCA mutated patients. The optimized niraparib price, economic status, and health insurance coverage may benefit the economic outcome.